Civic Crowdfunding A collective option for local public goods? - Charbit, Claire (OECD Regional Development Working Papers, 2017)
This paper investigates the potential of civic crowdfunding as an innovative and collective option for contributing to the production of local public goods. It is articulated around two pillars. The first section provides a general understanding of crowdfunding practices and focuses principally on its civic component. Civic crowdfunding should be distinguished from other types of crowdfunding since it pursues an objective of general interest and mainly concerns place-based projects instigated by citizens and civil society organisations. The aim of this section is to better understand this field, from the general principles to the specific characteristics of actors and their motivations. The second section goes a step further towards the analysis of this practice with regards to the provision of local public goods. Crowdfunded local public goods usually belong to a specific category of public goods, "urban commons", which generate significant challenges in terms of production, governance and sustainability. Building on the theory of contracts to better understand the interaction among stakeholders in this process, a new model of co-production relying on civic crowdfunding is proposed. Subnational governments would have a key role to play in enabling this practice and facilitating citizen empowerment through the mobilisation of platforms assets. Civic crowdfunding can provide opportunities for subnational governments in terms of citizens/user information, funding, communication, trust and territorial attractiveness. This paper outlines a series of key questions to guide policy makers in experimenting this practice